Peran Peran Relawan Dalam Meningkatkan Kesejahteraan Psikososial Anak di Panti Asuhan Harapan Mulia Purwokerto - Latifah Wulansari, Latifah Wulansari (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
The psychosocial well-being of children in orphanages is an important issue that requires attention, especially for those who face various social and emotional difficulties. The purpose of this activity is to find out how volunteers contribute to improving the psychosocial well-being of children at Harapan Mulia Orphanage Purwokerto. A total of 38 volunteers were involved in direct interaction with 15 children aged 4 to 16 years using a community education approach. The activities included emotional support, profession and aspiration class learning, creation class, group discussion, and educational games. The results showed how the volunteers were able to increase the children's self-esteem, reduce their loneliness, and inspire them to reach their full potential. The children were more inspired to achieve their goals and felt more cared for. It can be concluded that volunteers have an important role in promoting the emotional and social development of children in orphanages and supporting their psychosocial well-being.